The Effects of Brain Magnetic Resonance Imaging Indices in the Association of Olfactory Identification and Cognition in Chinese Older Adults - Tan, Ziyi; Wang, Yingzhe; Lu, Heyang; Tian, Weizhong; Xu, Kelin; Fan, Min; Zhao, Xiaolan; Jin, Li; Cui, Mei; Jiang, Yanfeng; Chen, Xingdong (Frontiers in Aging Neuroscience, 2022)
Background: Olfactory identification deficit frequently occurs in individuals with cognitive decline; however, a pathological mechanism linking the two has not been discovered. We aimed to study the association between olfactory identification and cognitive function, and determine the effects of brain regions atrophy therein. Methods: 645 individuals (57.5% were female) from the Taizhou Imaging Study, who underwent cognitive and olfactory identification measurements, were included. A subsample of participants underwent brain magnetic resonance imaging (n = 622). Cognition was assessed with a neuropsychological battery. Olfactory identification was measured using a 12-item Sniffin’ Sticks test. Beta and logistic regressions were used to elucidate the association between olfactory identification and cognition, and the effects of brain regions atrophy in this association. Results: Dementia was diagnosed in 41 (6.4%) individuals (mean age = 64.8 years), and mild cognitive impairment (MCI) in 157 (24.3%) individuals (mean age = 64.4 years). Olfactory identification was associated with MMSE and MoCA (both P < 0.001) and specific cognitive domains (memory, executive function, visuospatial function, and language; all P < 0.05). Higher olfactory identification was associated with lower likelihood of MCI and dementia (P < 0.05). The amygdala volume was significantly related to olfactory identification, MMSE, MoCA, and language, and could attenuate the association between olfactory identification and cognitive function. Conclusions: The association between olfactory identification and cognition can be partly attributable to differences in amygdala volume, suggesting that the amygdala could be a shared neural substrate that links olfactory identification and cognitive function. Limitations of this study include that all these results were based on a cross-sectional study.